2020
DOI: 10.1186/s12862-020-01681-w
|View full text |Cite
|
Sign up to set email alerts
|

Species delimitation in the cyanolichen genus Rostania

Abstract: Background In this study, we investigate species limits in the cyanobacterial lichen genus Rostania (Collemataceae, Peltigerales, Lecanoromycetes). Four molecular markers (mtSSU rDNA, β-tubulin, MCM7, RPB2) were sequenced and analysed with two coalescent-based species delimitation methods: the Generalized Mixed Yule Coalescent model (GMYC) and a Bayesian species delimitation method (BPP) using a multispecies coalescence model (MSC), the latter with or without an a priori defined guide tree. Results Species d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 87 publications
(140 reference statements)
2
14
0
Order By: Relevance
“…However, the identification of many taxa within some cyanobacterial orders remains difficult, and further research is needed to better elucidate the relationships among their members. Although some approaches for species identification are rarely used for cyanobacteria, they are increasingly being used for algae and cyanolichens (e.g., [24,25]). Species delimitation analyses using tree-based and non-tree-based methods have enabled the identification of novel species, and are being utilized as a substantive concept in current systematics [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the identification of many taxa within some cyanobacterial orders remains difficult, and further research is needed to better elucidate the relationships among their members. Although some approaches for species identification are rarely used for cyanobacteria, they are increasingly being used for algae and cyanolichens (e.g., [24,25]). Species delimitation analyses using tree-based and non-tree-based methods have enabled the identification of novel species, and are being utilized as a substantive concept in current systematics [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study (Košuthová et al 2020), we concluded through species delimitation analyses that the Rostania occultata complex consists of a minimum of four species, which we informally called R. occultata 1, R. occultata 2, R. occultata 3 and R. occultata 4,5,6. We tested and evaluated further potential candidate species within these informal species but found no distinct morphology, substratum ecology or geographical distribution to suggest that these genetically comparatively distinct but poorly sampled candidates should be treated as species.…”
Section: Resultsmentioning
confidence: 94%
“…Photobionts. Košuthová et al (2020) found a correlation between thallus morphology and the Nostoc morphotypes; species with granular thalli have Nostoc that produce either single cells or cells in small clusters (Fig. 1E), whereas species with lobate thalli have Nostoc with cells in short to long chains (Figs 2D & 4C).…”
Section: Observations Regarding Some Charactersmentioning
confidence: 93%
See 2 more Smart Citations